2021
DOI: 10.13057/nusbiosci/n130215
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of Jatropha tanjorensis leaf extracts against bacteria associated with wound infections from the clinical setting

Abstract: Abstract. Babayemi OO, Oke EA, Bayode MT. 2021. Antibacterial activity of Jatropha tanjorensis leaf extracts against bacteria associated with wound infections from the clinical setting. Nusantara Bioscience 13: 260-267. The use of microbial agents to treat infectious wounds based on ethnobotanical knowledge is still minimal. Antibacterial activity of Jatropha tanjorensis J.L.Ellis & Saroja leaf crude extracts and commercial antibiotics were evaluated against bacterial isolates associated with wound samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Chromolaena odorata leaves have been reported to contain various bioactive compounds that contribute to its antimicrobial potency, particularly against bacterial infections associated with post-operative wound swabs as similarly reported by Oladejo et al [35] who observed potent antibacterial activity of Jatropha tanjorensis leaf extracts against bacteria associated with wound infections from clinical settings in Ado-Ekiti. 1, 4-Dichlorobenzene is an aromatic compound with potential antimicrobial properties.…”
Section: Discussionmentioning
confidence: 61%
“…Chromolaena odorata leaves have been reported to contain various bioactive compounds that contribute to its antimicrobial potency, particularly against bacterial infections associated with post-operative wound swabs as similarly reported by Oladejo et al [35] who observed potent antibacterial activity of Jatropha tanjorensis leaf extracts against bacteria associated with wound infections from clinical settings in Ado-Ekiti. 1, 4-Dichlorobenzene is an aromatic compound with potential antimicrobial properties.…”
Section: Discussionmentioning
confidence: 61%
“…The earlier phytochemical screening revealed that phenols and polyphenols were strongly present in the C. aurea root extract in both the ethanol and methanol extracts 37 . In contrast to alkaloids and anthraquinone, saponin, tannin, flavonoid, steroid, and terpenoid were detected in the qualitative phytochemical analysis of Jatropha tanjorensis ethanol, methanol, and aqueous leaf extracts 38 . Another qualitative investigation found that Vernonia amygdalina leaf extracts in both aqueous and ethanol included tannins, saponins, alkaloids, oxalate, phylate, flavonoids, steroids, and phenols.…”
Section: Discussionmentioning
confidence: 82%
“…PROBIOTICS' liquid culture filtrates [100ul] were pipetted into the wells. The plates were then incubated at 37°C for at least 24 h.; the diameters of inhibition zone around the well were measured [14,15] .…”
Section: Antibacterial Activity Of Probiotics' Metabolitesmentioning
confidence: 99%